We are gathered here today [videorecording (DVD)] - Boyd, Paul; Huston, Danny, 1962-; Parker, Nicole Ari; Shaye, Lin, 1943-; O'Hara, Jenny (Freestyle Digital Media, 2022)
During the pandemic, a dying patriarch is hospitalized with COVID-19. His interracial family connects via video calls, where love, conflict, and long-buried secrets surface, reshaping their relationships in unexpected ways.